Ce-substituted Mg-Al layered double hydroxides to prolong the corrosion protection lifetime of aluminium alloys - Vieira, Daniel E. L. (2021)
Layered double hydroxides (LDH) have emerged as an alternative to chromates for corrosion protection by exploiting anion-exchange phenomena: the LDH releases corrosion inhibitor anions and captures the corrosive agent anions, extending the metal surface lifetime. In this work, the main aim was to promote continuation of corrosion protection after the end of the process of anion-exchange. For this purpose, cerium cations, which possess corrosion protection capability, were incorporated in the LDH structure via partial substitution of aluminium cations. The changes occurring to the LDH in solution after exposure for an extended period of 30 days to UV radiation, were evaluated. The study was performed using Mg3Al1-xCex LDH intercalated with nitrate, where x was 7.5 mol%, Ce3+ release from the hydroxide layers being promoted by UV-radiation-induced LDH degradation. The release of Ce3+ from the hydroxide layers was quantified by UV-visible spectroscopy. The continued corrosion protection of aluminium alloy 2024 immersed in a solution with and without the presence of degraded LDH was examined by electrochemical impedance spectroscopy and surface analysis.